Is There Relationships of Investment, Risk, Efficiency Levels of Financial Performance in Sharia Insurance in Indonesia? - Deni Pandu Nugraha; Hepi Prayudiawan; Eris Sudariswan (Institute of Computer Science (IOCS), 2021)
The purpose of this study is to analyze the effect of Premium Growth, Investment Return, Leverage, Loss Claim Ratio. Healthy level with the value of Risk-Based Capital, and the Level of Efficiency on the Growth of Return On Assets (ROA) in Sharia Insurance Companies in Indonesia. The sample in this study was 34 Sharia Insurance Companies in Indonesia in 2013-2017. This study uses panel data regression analysis with Eviews version 9. sample data collection technique using purposive sampling. The results of this study indicate that simultaneously the independent variable influences the effect of Premium Growth, Investment Return, Leverage, Loss Claims Ratio, Healthy Level with Risk-Based Capital, and Efficiency Level has a significant effect on Return on Assets (ROA). Partially the results show that Investment Results, Leverage, Loss Claims Ratio, and Efficiency Levels influence Return On Assets (ROA), while Premium Growth and Soundness with Risk-Based Capital values have no effect on Return On Assets (ROA) with a significance level.